"T.E. Lawrence" in Arabia and after - Liddell Hart, Basil Henry, Sir, 1895-1970. (Westport, Conn. : Greenwood Press, 1979)
T.E. Shaw, better known as Lawrence of Arabia, was one of the most romantic, heroic, and enigmatic figures of his day. The subject of myth and hagiography, he was equally accomplished in several fields--as archaeologist, diplomat, writer, and soldier--and he worked throughout World War I and after in the Middle East in efforts to promote independent Arab states. His autobiography Seven Pillars of Wisdom is one of the greatest works of its kind. The esteemed military historian B.H. Liddell Hart wrote this study of Lawrence in order to pierce the clouds of legend. He discussed Lawrence's Oxford days, his experiences as an intelligence officer in Egypt, and in particular the tactics of guerrilla warfare he practiced so effectively against the large Turkish armies during World War I. Liddell Hart was one of the few to give Lawrence his full justice as both a man and a brilliant soldier. Long out-of-print, this book unravels the many puzzling features of Lawrence's story and restores him to his proper place as one of the twentieth century's heroic, but very human, figures.
Reprint of the 1935 new and rev. ed. published by J. Cape, London.
American ed. published in 1935 under title: Colonel Lawrence, the man behind the legend.
Keywords: Lawrence, T. E. -- 1888-1935.; Lawrence, T. E. -- 1888-1935.; 1900-1999; World War, 1914-1918 -- Campaigns -- Arabian Peninsula; British -- Middle East -- History -- 20th century; Middle East specialists -- Great Britain -- Biography; Archaeologists -- Middle East -- Biography; Soldiers -- Great Britain -- Biography; Archaeologists; British; Middle East specialists; Military campaigns; Soldiers; Great Britain; Middle East; Biography; Biographies; History